Influence of genotype and bacterization on growth, development, and soluble carbohydrate content in soybean E-genes isogenic lines - D. Hlushach; V. Zhmurko; O. Avksentieva (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія, 2023)
Photoperiod, which regulates the duration of vegetative and generative development, and the plant-microorganism interaction, which influences the metabolic status of plant organisms, are important factors in the regulating plant growth and development. The aim of the study was to determine the influence of Glycine max (L.) Merr. genotype and seed pre-bacterization with a virulent and active strain of Bradyrhizobium japonicum 634b on the plant growth and development, and on the soluble carbohydrate content in leaves of isogenic by E-genes lines under field conditions. Nearly isogenic lines (NILs) of soybean, in which the E1, E2, and E3 genes are located at different allelic loci, were used. Sterile seeds were pretreated with distilled water (control) and Bradyrhizobium japonicum 634b cell suspension (experiment). Plants were grown under natural long-day conditions (16 hours). The growth and development of the soybean were evaluated by phenological observations, morphometric indicators fixed at the V3 and V5 developmental stages, relative growth rate (RGR), and the content of soluble sugars ‒ mono- and oligosaccharides. The effect of the factors studied (genotype, bacterization, and their interaction) was calculated. The results of the experiment and the calculation of the effect of the factor showed that the isoline genotype has the greatest effect on seed germination, phenological development of the plant and duration of the VE-R1 phase, growth of the root system in the V3 and V5 phases, and the content of monosaccharides involved in forming the plant-microorganism interaction. The effect of bacterization is most evident in the RGR, shoot development, and the oligosaccharide content of the leaves of NILs in the V3 and V5 phases. Among the isolines studied, L 80-5879, which has the E1 gene (flowering repressor) in a dominant state, was characterized by minimal sensitivity to bacterization. It was found that bacterization and genotype interaction didn't influence the VE-R1 duration stage and the shoot and root length. The results obtained therefore prove that the E-series genes, which determine the photoperiodic sensitivity of soya beans, can also be indirectly involved in establishing plant-microorganism interactions.